Multidrug-Resistant Bacteria from Raw Meat of Buffalo and Chicken, Nepal - Bhuvan Saud; Govinda Paudel; Sharmila Khichaju; Dipendra Bajracharya; Gunaraj Dhungana; Mamata Sherpa Awasthi; Vikram Shrestha (Veterinary Medicine International, 2019)
Antimicrobial resistance is a major global issue for human and animals. Increased use of antimicrobials in livestock and poultry has become one of the causes of antimicrobial resistance development in microorganisms. The aim of the study was to characterize antimicrobial resistant bacteria from raw buffalo and chicken meat in standard in vitro condition. A total of 140 raw meat samples were collected from different retail shops of Bhaktapur Metropolitan City, Nepal. Among them, 70 were raw buffalo meat and 70 were raw chicken meat samples. Bacterial growth, identification, and antimicrobial susceptibility test were performed according to Clinical & Laboratory Standards Institute (CLSI) guidelines. Out of 140 samples, bacterial growth was seen in 67 raw buffalo meat and 59 raw chicken meat samples, i.e., bacterial growth was observed in 90.0% of the samples. A total of 161 bacterial isolates were detected. Escherichia coli (35.4%) and Klebsiella spp. (30.4%) were found to be the most prevalent bacteria followed by Citrobacter spp. (11.8%), Staphylococcus aureus (9.3%), Salmonella spp. (7.4%), and Proteus spp. (5.5%). Chicken meat isolates showed higher antimicrobial resistance rates in comparison to buffalo meat isolates, particularly against antimicrobials like Amoxicillin, Tetracycline, Cotrimoxazole and Nalidixic acid, p value<0.05 when compared between buffalo and chicken meat. Overall, 32.7% Multidrug-Resistant (MDR) isolates were found, in which 50.0% MDR isolates were found from chicken raw meat and 21.9% were found from buffalo raw meat. MDR isolates of Escherichia coli, Proteus spp. and Staphylococcus aureus constituted 52.5%, 77.7% and 40.0%, respectively, of both buffalo and chicken raw meat. This study indicates antimicrobials resistant bacteria existing at an alarming rate, higher in chicken meat than in buffalo meat.